Hot-rolled steel sheet
By adjusting the chemical composition and metal structure of the hot-rolled steel plate, the problems of insufficient ductility, fatigue characteristics and shear processing properties of high-strength steel plates in the prior art are solved, and high strength and excellent multiple properties are achieved.
Patent Information
- Application Number
- CN202380061905.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-29
- Filing Date
- 2023-08-29
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to take into account the ductility, fatigue characteristics and shear processing properties of high-strength steel plates.
By adjusting the chemical composition and metal structure of the hot-rolled steel plate, it is ensured that it contains elements of a specific range (such as C, Si, Mn, Ti, Nb, V, etc.), and controls the area ratio of ferrite, the average spherical equivalent radius and average number density of alloy carbides, and the periodicity and uniformity of the metal structure.
The excellent ductility, fatigue characteristics and shear processing properties of high-strength steel plates are achieved, making them suitable for automotive components and other mechanical structures.
Smart Images

Figure CN119768550A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a hot-rolled steel sheet, and more specifically to a hot-rolled steel sheet that is formed into various shapes by press working or the like and is particularly related to a hot-rolled steel sheet that is high in strength and excellent in ductility, fatigue properties, and shear workability.
[0002] This application claims priority based on Japanese Patent Application No. 2022-135960 filed in Japan on August 29, 2022, the contents of which are incorporated herein by reference. Background Art
[0003] In recent years, efforts have been made to reduce carbon dioxide emissions in many fields from the perspective of protecting the global environment. Automobile manufacturers are also actively developing technologies to reduce vehicle weight for the purpose of reducing fuel consumption. However, in order to ensure the safety of passengers, the focus is also on improving collision resistance, so reducing vehicle weight is not easy.
[0004] In order to balance the lightweight of the vehicle body with the anti-collision characteristics, the use of high-strength steel plates to thin the components is being studied. Therefore, there is an urgent need for steel plates that have both high strength and excellent formability. In order to meet these requirements, several technologies have been proposed so far. In order to meet these requirements, several technologies have been proposed so far. Since there are various processing methods for automobile components, the required formability varies depending on the components used, and among them, ductility is positioned as an important indicator of formability.
[0005] In addition, automobile components are formed by stamping, and the blanks formed by stamping are often manufactured by shearing with high productivity. The blanks manufactured by shearing need to have excellent end surface accuracy after shearing. For example, once the end surface (shear end surface) after shearing produces a secondary shear surface of shear surface-fracture surface-shear surface, the accuracy of the shear end surface deteriorates significantly.
[0006] For example, Patent Document 1 discloses a high-strength steel sheet having a second phase composed of retained austenite and / or martensite finely dispersed in grains, excellent in ductility and stretch flangeability, and having a tensile strength of 980 MPa or more.
[0007] Patent Document 2 discloses a method of reducing the ferrite grain size d of the surface layer by s The ferrite grains inside b The ratio of d s / d b The technology of controlling the burr height after punching to below 0.95.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2005-179703
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 10-168544
[0012] Non-patent literature
[0013] Non-patent document 1: J. Webel, J. Gola, D. Britz, F. Mucklich, Materials Characterization 144 (2018) 584-596
[0014] Non-patent document 2: DL Naik, HU Sajid, R. Kiran, Metals 2019, 9, 546
[0015] Non-patent document 3: K. Zuiderveld, Contrast Limited Adaptive Histogram Equalization, Chapter VIII.5, Graphics Gems IV. PS Heckbert (Eds.), Cambridge, MA, Academic Press, 1994, pp. 474-485 Summary of the invention
[0016] Problems to be solved by the invention
[0017] The techniques disclosed in Patent Documents 1 and 2 are both techniques for improving either ductility or the end surface properties after shearing. However, Patent Documents 1 and 2 do not mention techniques for achieving both of these properties.
[0018] Furthermore, high-strength steel sheets are sometimes required to have more excellent fatigue properties.
[0019] The present invention has been made in view of the above-mentioned problems in the prior art, and an object of the present invention is to provide a hot-rolled steel sheet having high strength and excellent ductility, fatigue properties, and shear workability.
[0020] Means used to solve problems
[0021] The gist of the present invention is as follows.
[0022] (1) The chemical composition of the hot-rolled steel sheet according to one embodiment of the present invention contains, by mass %, the following:
[0023] C: 0.050~0.250%,
[0024] Si: 0.05-3.00%,
[0025] Mn: 1.00~4.00%,
[0026] One or more of Ti, Nb and V: 0.060 to 0.500% in total,
[0027] Sol.Al: 0.001~2.000%,
[0028] P: 0.100% or less,
[0029] S: 0.0300% or less,
[0030] N: 0.1000% or less,
[0031] O: 0.0100% or less,
[0032] Cu: 0-2.00%,
[0033] Cr: 0~2.00%,
[0034] Mo: 0-1.00%,
[0035] Ni: 0-2.00%,
[0036] B: 0~0.0100%,
[0037] Ca: 0~0.0200%,
[0038] Mg: 0~0.0200%,
[0039] REM: 0~0.1000%、
[0040] Bi: 0~0.0200%,
[0041] As: 0~0.100%,
[0042] One or more of Zr, Co, Zn and W: 0 to 1.00% in total, and Sn: 0 to 0.05%,
[0043] The remainder contains Fe and impurities,
[0044] Metallic structure is calculated by area %,
[0045] Retained austenite is less than 3.0%,
[0046] Ferrite is 15.0% or more and less than 60.0%,
[0047] Pearlite is less than 5.0%,
[0048] The average spherical equivalent radius of the alloy carbides in the ferrite is greater than 0.5 nm and less than 10.0 nm, and the average number density is 0.10×10 16 Pieces / cm3 Above and less than 1.45×10 16 Pieces / cm 3 ,
[0049] The E value indicating the periodicity of the metal structure is 10.7 or more.
[0050] The I value indicating the uniformity of the metal structure is 1.020 or more.
[0051] The standard deviation of the Mn concentration was 0.60 mass % or less.
[0052] (2) According to the hot-rolled steel sheet described in (1) above, the chemical composition may contain, by mass %, one or more selected from the group consisting of the following elements:
[0053] Cu: 0.01-2.00%,
[0054] Cr: 0.01~2.00%,
[0055] Mo: 0.01~1.00%,
[0056] Ni: 0.02-2.00%,
[0057] B: 0.0001~0.0100%,
[0058] Ca: 0.0005~0.0200%,
[0059] Mg: 0.0005~0.0200%,
[0060] REM: 0.0005~0.1000%、
[0061] Bi: 0.0005 to 0.0200%, and
[0062] As: 0.001~0.100%.
[0063] Effects of the Invention
[0064] According to the above aspects of the present invention, a hot-rolled steel sheet having high strength and excellent ductility, fatigue properties, and shear workability can be obtained.
[0065] The hot-rolled steel sheet according to the above aspect of the present invention is suitable as an industrial raw material for automobile components, machine structural components, and further, building components. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 This is an example of a sheared end surface of a hot-rolled steel sheet according to an example of the present invention.
[0067] Figure 2This is an example of a sheared end surface of a hot-rolled steel sheet of a comparative example. DETAILED DESCRIPTION
[0068] The chemical composition and metal structure of the hot-rolled steel sheet of this embodiment will be described in more detail below. However, the present invention is not limited to the embodiments disclosed in this embodiment, and various modifications can be made without departing from the gist of the present invention.
[0069] Regarding the numerical ranges described below with "to", the lower limit and upper limit are included in the range. Regarding the numerical values expressed as "less than" or "greater than", the values are not included in the numerical range. In the following description, % related to the chemical composition of the steel plate is mass % unless otherwise specified.
[0070] Chemical composition
[0071] The hot rolled steel sheet of the present embodiment contains, by mass%, C: 0.050-0.250%, Si: 0.05-3.00%, Mn: 1.00-4.00%, one or more of Ti, Nb and V: 0.060-0.500% in total, sol.Al: 0.001-2.000%, P: 0.100% or less, S: 0.0300% or less, N: 0.1000% or less, O: 0.0100% or less, and the remainder: Fe and impurities. Each element is described in detail below.
[0072] C: 0.050~0.250%
[0073] C improves the strength of ferrite by increasing the area ratio of the hard phase and combining with precipitation strengthening elements such as Ti, Nb, and V. When the C content is less than 0.050%, the desired strength cannot be obtained. Therefore, the C content is set to 0.050% or more. The C content is preferably 0.060% or more, more preferably 0.070% or more, and further preferably greater than 0.070%, 0.075% or more, or 0.080% or more.
[0074] On the other hand, when the C content exceeds 0.250%, the area ratio of ferrite decreases, resulting in reduced ductility of the hot-rolled steel sheet. Therefore, the C content is set to 0.250% or less. The C content is preferably 0.200% or less, 0.180% or less, or 0.150% or less.
[0075] Si: 0.05~3.00%
[0076] Si has the effect of promoting the formation of ferrite to improve the ductility of the hot-rolled steel sheet, and the effect of strengthening the ferrite solid solution to improve the strength of the hot-rolled steel sheet. In addition, Si has the effect of making the steel sound by deoxidation (suppressing the generation of defects such as pores in the steel). When the Si content is less than 0.05%, the effect based on the above-mentioned effect cannot be obtained. Therefore, the Si content is set to 0.05% or more. The Si content is preferably 0.50% or more, and more preferably 0.80% or more.
[0077] On the other hand, when the Si content exceeds 3.00%, the surface properties and chemical conversion treatability of the steel sheet, and further the ductility and weldability, are significantly deteriorated, and A 3 The transformation point rises significantly. This makes it difficult to perform hot rolling stably. Therefore, the Si content is set to 3.00% or less. The Si content is preferably 2.50% or less, and more preferably 2.00% or less or 1.50% or less.
[0078] Mn: 1.00~4.00%
[0079] Mn has the effect of inhibiting ferrite transformation and improving the strength of hot-rolled steel sheets. When the Mn content is less than 1.00%, the desired tensile strength cannot be obtained. Therefore, the Mn content is set to 1.00% or more. The Mn content is preferably 1.30% or more, and more preferably 1.50% or more.
[0080] On the other hand, when the Mn content exceeds 4.00%, the morphology of the hard phase becomes periodic bands due to the segregation of Mn, and it becomes difficult to obtain the desired shear workability. Therefore, the Mn content is set to 4.00% or less. The Mn content is preferably 3.50% or less, and more preferably 3.00% or less or 2.50% or less.
[0081] One or more of Ti, Nb and V: 0.060 to 0.500% in total,
[0082] Ti, Nb and V precipitate finely in steel as carbides and nitrides, and improve the strength of steel by precipitation strengthening. Furthermore, they are elements required to obtain the desired fatigue properties. When the total content of Ti, Nb and V is less than 0.060%, these effects cannot be obtained. Therefore, the total content of Ti, Nb and V is set to 0.060% or more. It should be noted that it is not necessary to contain all of Ti, Nb and V, as long as any one of them is contained, and its content is 0.060% or more. The total content of Ti, Nb and V is preferably 0.080% or more, more preferably 0.100% or more, and further preferably 0.120% or more.
[0083] On the other hand, when the total content of Ti, Nb and V exceeds 0.500%, the workability of the hot-rolled steel sheet deteriorates. Therefore, the total content of Ti, Nb and V is set to 0.500% or less. Preferably, it is 0.300% or less, more preferably 0.250% or less, and further preferably 0.200% or less.
[0084] Sol.Al: 0.001~2.000%
[0085] Al, like Si, has the effect of improving steel health by deoxidation, and has the effect of promoting ferrite formation and improving the ductility of hot-rolled steel sheets. When the sol.Al content is less than 0.001%, the effect based on the above-mentioned effect cannot be obtained. Therefore, the sol.Al content is set to 0.001% or more. The sol.Al content is preferably 0.010% or more, and more preferably 0.020% or more or 0.030% or more.
[0086] On the other hand, when the sol.Al content exceeds 2.000%, the above effect is saturated and it is not economically preferable, so the sol.Al content is set to 2.000% or less. The sol.Al content is preferably 0.400% or less, more preferably 0.300% or less, and further preferably 0.250% or less.
[0087] It should be noted that sol.Al represents acid-soluble Al, and represents solid-solution Al present in the steel in a solid-solution state.
[0088] P: 0.100% or less
[0089] P is also an element that has the effect of improving the strength of the hot-rolled steel sheet by solid solution strengthening. Therefore, P can be actively contained. However, P is an element that is prone to segregation. When the P content is greater than 0.100%, the reduction in ductility caused by grain boundary segregation becomes significant. Therefore, the P content is set to 0.100% or less. The P content is preferably 0.030% or less. The lower limit of the P content does not need to be specifically specified, but is preferably set to 0.001% from the perspective of refining cost.
[0090] S: 0.0300% or less
[0091] S forms sulfide inclusions in steel and reduces the ductility of the hot-rolled steel sheet. When the S content exceeds 0.0300%, the ductility of the hot-rolled steel sheet is significantly reduced. Therefore, the S content is set to 0.0300% or less. The S content is preferably 0.0050% or less. The lower limit of the S content does not need to be particularly specified, but is preferably set to 0.0001% from the perspective of refining cost.
[0092] N: 0.1000% or less
[0093] N has the effect of reducing the ductility of the hot-rolled steel sheet. When the N content is greater than 0.1000%, the ductility of the hot-rolled steel sheet is significantly reduced. Therefore, the N content is set to 0.1000% or less. The N content is preferably less than 0.0800%, more preferably less than 0.0700%, and further preferably less than 0.0050%. The lower limit of the N content does not need to be specifically specified. In the case of containing one or more of Ti, Nb and V to further refine the metal structure, in order to promote the precipitation of carbonitrides, the N content is preferably set to 0.0010% or more, and more preferably set to 0.0020% or more.
[0094] O: 0.0100% or less
[0095] If O is contained in a large amount in steel, it will form coarse oxides that become the starting point of destruction, causing brittle fracture and hydrogen cracking. Therefore, the O content is set to 0.0100% or less. The O content is preferably 0.0080% or less, more preferably 0.0055% or less, and further preferably 0.0050% or less. In order to disperse a large amount of fine oxides during deoxidation of molten steel, the O content can be set to 0.0005% or more or 0.0010% or more.
[0096] The remainder of the chemical composition of the hot-rolled steel sheet of the present embodiment may be Fe and impurities. In the present embodiment, impurities refer to substances mixed from ore, waste materials, or manufacturing environment as raw materials, and / or substances allowed within a range that does not adversely affect the hot-rolled steel sheet of the present embodiment.
[0097] The hot-rolled steel sheet of the present embodiment may contain the following elements as optional elements in place of a portion of Fe. When these optional elements are not contained, the lower limit of the content is 0%. The optional elements will be described in detail below.
[0098] Cu: 0.01~2.00%
[0099] Cr: 0.01~2.00%
[0100] Mo: 0.01~1.00%
[0101] Ni: 0.02~2.00%
[0102] B: 0.0001~0.0100%
[0103] Cu, Cr, Mo, Ni and B all have the effect of improving the hardenability of the hot-rolled steel sheet. In addition, Cu and Mo have the effect of precipitating into the steel as carbides to improve the strength of the hot-rolled steel sheet. Furthermore, Ni has the effect of effectively suppressing the grain boundary cracking of the slab caused by Cu when Cu is contained. Therefore, one or more of these elements may be contained.
[0104] As described above, Cu has the effect of improving the hardenability of hot-rolled steel sheets and the effect of precipitating into steel as carbides at low temperatures to improve the strength of hot-rolled steel sheets. In order to more reliably obtain the effects based on the above effects, the Cu content is preferably set to 0.01% or more, and more preferably set to 0.05% or more. However, when the Cu content is greater than 2.00%, grain boundary cracking of the slab sometimes occurs. Therefore, the Cu content is set to 2.00% or less. The Cu content is preferably 1.50% or less, and more preferably 1.00% or less.
[0105] As mentioned above, Cr has the effect of improving the hardenability of hot-rolled steel sheets. In order to more reliably obtain the effect based on the above-mentioned effect, it is preferred to set the Cr content to 0.01% or more, and more preferably to 0.05% or more. However, when the Cr content is greater than 2.00%, the chemical conversion treatability of the hot-rolled steel sheet is significantly reduced. Therefore, the Cr content is set to 2.00% or less.
[0106] As mentioned above, Mo has the effect of improving the hardenability of the hot-rolled steel sheet and the effect of precipitating into the steel as a carbide to improve the strength of the hot-rolled steel sheet. In order to more reliably obtain the effect based on the above-mentioned effect, it is preferred to set the Mo content to 0.01% or more, and more preferably to 0.02% or more. However, even if the Mo content is set to more than 1.00%, the effect based on the above-mentioned effect is saturated, which is not economically preferred. Therefore, the Mo content is set to 1.00% or less. The Mo content is preferably 0.50% or less, and more preferably 0.20% or less.
[0107] As mentioned above, Ni has the effect of improving the hardenability of hot-rolled steel sheets. In addition, when Ni contains Cu, it has the effect of effectively suppressing the grain boundary cracking of the slab caused by Cu. In order to more reliably obtain the effect based on the above-mentioned effect, the Ni content is preferably set to 0.02% or more. Since Ni is an expensive element, it is not economically preferable to contain a large amount of Ni. Therefore, the Ni content is set to 2.00% or less.
[0108] As mentioned above, B has the effect of improving the hardenability of hot-rolled steel sheets. In order to more reliably obtain the effect based on this effect, it is preferred to set the B content to 0.0001% or more, and more preferably to 0.0002% or more. However, when the B content is greater than 0.0100%, the formability of the hot-rolled steel sheet is significantly reduced, so the B content is set to 0.0100% or less. The B content is preferably set to 0.0050% or less.
[0109] Ca: 0.0005~0.0200%
[0110] Mg: 0.0005~0.0200%
[0111] REM: 0.0005~0.1000%
[0112] Bi: 0.0005~0.0200%
[0113] Ca, Mg and REM all have the effect of improving the ductility of the hot-rolled steel sheet by adjusting the shape of the inclusions in the steel to a preferred shape. In addition, Bi has the effect of improving the ductility of the hot-rolled steel sheet by refining the solidification structure. Therefore, one or more of these elements may be contained. In order to more reliably obtain the effects based on the above effects, it is preferred to set any one or more of Ca, Mg, REM and Bi to 0.0005% or more. However, when the Ca content or the Mg content is greater than 0.0200% or the REM content is greater than 0.1000%, inclusions are sometimes excessively generated in the steel, which in turn reduces the ductility of the hot-rolled steel sheet. In addition, even if the Bi content is set to be greater than 0.0200%, the effect based on the above effects is saturated, which is not economically preferred. Therefore, the Ca content and the Mg content are set to less than 0.0200%, the REM content is set to less than 0.1000%, and the Bi content is set to less than 0.0200%. The Bi content is preferably 0.0100% or less.
[0114] Here, REM refers to a total of 17 elements consisting of Sc, Y and lanthanoid elements, and the above-mentioned REM content refers to the total content of these elements. Lanthanoid elements are added in the form of mixed rare earth alloys in industry.
[0115] As: 0.001~0.100%
[0116] As contributes to improving the ductility of the hot-rolled steel sheet by reducing the austenite single-phase transformation temperature and refining the prior austenite grains. In order to reliably obtain this effect, the As content is preferably set to 0.001% or more.
[0117] On the other hand, even if a large amount of As is contained, the above-mentioned effect is saturated, so the As content is made 0.100% or less.
[0118] One or more of Zr, Co, Zn and W: 0 to 1.00% in total
[0119] Sn: 0~0.05%
[0120] Regarding Zr, Co, Zn and W, the present inventors have confirmed that even if these elements are contained in an amount of 1.00% or less in total, the effect of the hot-rolled steel sheet of the present embodiment is not impaired. Therefore, one or more of Zr, Co, Zn and W may be contained in an amount of 1.00% or less in total.
[0121] The present inventors have confirmed that the effect of the hot-rolled steel sheet of the present embodiment is not impaired even if a small amount of Sn is contained. However, if a large amount of Sn is contained, flaws may occur during hot rolling, so the Sn content is set to 0.05% or less.
[0122] The chemical composition of the hot-rolled steel sheet can be measured by conventional analytical methods. For example, ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry) can be used for measurement. It should be noted that sol.Al can be measured by ICP-AES using the filtrate after the sample is heated and decomposed with acid. C and S can be measured using the combustion-infrared absorption method, N using the inert gas melting-thermal conductivity method, and O using the inert gas melting-non-dispersive infrared absorption method.
[0123] When the hot-rolled steel sheet has a plating layer, a coating film, etc. on the surface, the chemical composition analysis is performed after the plating layer, the coating film, etc. are removed by mechanical grinding or the like as needed.
[0124] Metal structure of hot rolled steel plate
[0125] Next, the metal structure of the hot-rolled steel sheet according to the present embodiment will be described.
[0126] The metal structure of the hot-rolled steel sheet according to the present embodiment is, by area%, less than 3.0% of retained austenite, 15.0% or more and less than 60.0% of ferrite, less than 5.0% of pearlite, and the average spherical equivalent radius of alloy carbides in ferrite is 0.5 nm or more and less than 10.0 nm, and the average number density is 0.10×10 16 Pieces / cm 3 Above and less than 1.45×10 16 Pieces / cm 3 , the E value indicating the periodicity of the metal structure is greater than 10.7, the I value indicating the uniformity of the metal structure is greater than 1.020, and the standard deviation of the Mn concentration is less than 0.60 mass %.
[0127] Since the hot-rolled steel sheet of the present embodiment has the above-described metal structure, it is possible to obtain high strength as well as excellent ductility, fatigue properties, and shear workability.
[0128] It should be noted that this embodiment specifies the structural fraction of the metal structure in the region (rolling direction is any position) at the 1 / 4 position from the surface in the plate thickness direction of the hot rolled steel plate and at the 1 / 4 position from the end face in the direction perpendicular to the rolling direction and the plate thickness direction (plate width direction), the average spherical equivalent radius and average number density of alloy carbides, the E value, the I value, and the standard deviation of the Mn concentration. The reason is that the metal structure at this position represents the representative metal structure of the steel plate.
[0129] In addition, when the hot-rolled steel sheet has a plating layer, a coating film, etc., the "surface" mentioned here refers to the interface between the plating layer and the steel sheet.
[0130] Area ratio of retained austenite: less than 3.0%
[0131] Retained austenite is a metal structure that exists as a face-centered cubic lattice even at room temperature. Retained austenite has the effect of improving the ductility of hot-rolled steel sheets through transformation induced plasticity (TRIP). On the other hand, since retained austenite will transform into high-carbon martensite during shearing, it will hinder the generation of stable cracks and become the cause of the formation of secondary shear planes. When the area ratio of retained austenite is more than 3.0%, the above-mentioned effect becomes obvious and the shear workability of the hot-rolled steel sheet deteriorates. Therefore, the area ratio of retained austenite is set to less than 3.0%. The area ratio of retained austenite is preferably less than 1.5%, and more preferably less than 1.0%. The less retained austenite, the better, so the area ratio of retained austenite can be 0%.
[0132] The area ratio of retained austenite can be measured by X-ray diffraction, EBSP (Electron Back Scattering Diffraction Pattern) analysis, a method based on magnetic measurement, etc. In the present embodiment, the area ratio of retained austenite is measured by X-ray diffraction.
[0133] Regarding the determination of the area ratio of retained austenite by X-ray diffraction in the present embodiment, first, on the cross section at the 1 / 4 position from the surface in the thickness direction of the hot-rolled steel plate, a sample is obtained in such a way that the metal structure in the area of 1 mm or more at any position in the rolling direction and 1 mm or more centered at the 1 / 4 position from the end face in the plate width direction can be observed. For the above sample, the integrated intensity of 6 peaks, α(110), α(200), α(211), γ(111), γ(200), and γ(220), is obtained using Co-Kα rays. Next, the volume ratio of retained austenite is obtained using the intensity averaging method based on the above integrated intensity, which is regarded as the area ratio of retained austenite.
[0134] Area ratio of ferrite: 15.0% or more and less than 60.0%
[0135] Ferrite is a structure formed when the fcc phase changes to bcc at a relatively high temperature. Ferrite has a high working hardening rate, so it has the effect of improving the strength-ductility balance of the hot-rolled steel sheet. In order to obtain the above effect, the area ratio of ferrite is set to 15.0% or more. The area ratio of ferrite is preferably 20.0% or more, more preferably 25.0% or more, and further preferably 30.0% or more.
[0136] On the other hand, since ferrite has low strength, if the area ratio is too large, the desired strength cannot be obtained. Therefore, the ferrite area ratio is set to less than 60.0%, preferably 50.0% or less, and more preferably 45.0% or less.
[0137] Area ratio of pearlite: less than 5.0
[0138] Pearlite is a layered metal structure obtained by cementite precipitating in layers between ferrite, and is also a softer metal structure than bainite and martensite. When the area ratio of pearlite is 5.0% or more, carbon is consumed by cementite contained in pearlite, and the strength of martensite and bainite as the remaining structure is reduced, and the desired strength cannot be obtained. Furthermore, at the interface between ferrite and cementite contained in pearlite, micropores that deteriorate ductility are generated at an early stage, so when the area ratio of pearlite is 5.0% or more, the desired ductility and fatigue properties cannot be obtained. Therefore, the area ratio of pearlite is set to less than 5.0%. The area ratio of pearlite is preferably 3.0% or less. In order to improve the stretch flangeability of hot-rolled steel sheets, the area ratio of pearlite is preferably reduced as much as possible, and the area ratio of pearlite is further preferably 0%.
[0139] It should be noted that in the steel plate of this embodiment, the remaining structure other than retained austenite, ferrite and pearlite includes a hard structure composed of one or more of bainite, martensite and tempered martensite with a total area ratio of 32.0% or more and less than 85.0%.
[0140] The area ratio of the metal structure other than retained austenite is determined by the following method. First, at a position 1 / 4 from the end face in the plate width direction of the hot-rolled steel plate, a sample is obtained in a manner that allows the metal structure in the region of the section parallel to the rolling direction and the position 1 / 4 from the surface in the plate thickness direction to be observed. Although it also depends on the measuring device, the sample is a size that can be observed in the rolling direction of about 10 mm. Then, after the observation section of the above sample is polished to form a mirror surface, it is polished for 8 minutes at room temperature using colloidal silica without an alkaline solution to remove the strain introduced into the surface layer of the sample. For an area of more than 200 μm at any position in the rolling direction of the above observation section and more than 200 μm centered on the position 1 / 4 from the surface in the plate thickness direction, the measurement is performed by electron backscatter diffraction at a measurement interval of 0.1 μm to obtain crystal orientation information. The above measurement uses an EBSD analysis device consisting of a thermal field emission scanning electron microscope (JSM-7001F manufactured by JEOL) and an EBSD detector (DVC5 detector manufactured by TSL). At this time, the vacuum degree in the EBSD analysis device was set to 9.6×10 -5 Pa or less, the acceleration voltage was set to 15 kV, the irradiation current level was set to 13, and the irradiation level of the electron beam was set to 62.
[0141] Furthermore, a reflected electron image is taken under the same field of view. First, the grains in which ferrite and cementite are precipitated in layers are determined based on the reflected electron image, and the area ratio of the grains is calculated, thereby obtaining the area ratio of pearlite. Then, for the grains after excluding the grains judged to be pearlite, the obtained crystal orientation information is used using the "Grain Average Misorientation" function carried in the software "OIM Analysis (registered trademark)" attached to the EBSD analysis device, and the area with a Grain Average Misorientation value of less than 1.0° is judged to be ferrite. At this time, the Grain Tolerance Angle is set to 15°, and the area of the area judged to be ferrite is obtained, thereby obtaining the area ratio of ferrite.
[0142] The area ratio of the remaining structure is obtained by subtracting the area ratios of retained austenite, pearlite and ferrite from 100%. It should be noted that, based on the chemical composition and manufacturing conditions of the hot-rolled steel sheet, it can be inferred that the remaining structure is a hard structure formed by one or more of bainite, martensite and tempered martensite.
[0143] It should be noted that the rolling direction of the hot-rolled steel sheet is determined by the following method.
[0144] First, a test piece is obtained in such a way that the plate thickness section of the hot-rolled steel plate can be observed. The plate thickness section of the obtained test piece is mirror-polished, corroded with a saturated aqueous solution of picric acid, and then observed using an optical microscope. The observation range is set to the entire plate thickness, and the extension direction of the grains is determined. Here, the angle difference between the extension direction and the plate thickness direction is recorded as θ. Furthermore, at the surface at the 1 / 4 position of the plate thickness perpendicular to the plate thickness direction and parallel to the above-mentioned extension direction, the plate thickness section is polished in the same manner as the plate thickness section to determine the extension direction of the grains. Here, the angle difference between the plate thickness section and the extension direction is recorded as φ. In the spherical coordinate system with the plate thickness direction as the Z axis according to ISO3785, the direction of the deflection angle of θ and φ obtained according to the extension direction of the grains in the above two sections is determined as the rolling direction. The extension direction θ and φ can be determined by using the "Analyze Particles" function of the image analysis software "ImageJ" to set the Circularity to less than 0.7 to obtain the extension direction of the grains.
[0145] Average spherical equivalent radius of alloy carbides in ferrite: 0.5 nm or more and less than 10.0 nm
[0146] The hot-rolled steel sheet of this embodiment preferably controls the average spherical equivalent radius and average number density of the alloy carbides in the ferrite. When the average spherical equivalent radius of the alloy carbides in the ferrite is less than 0.5 nm, the strength of the ferrite relative to repeated deformation cannot be fully improved, and the desired fatigue strength cannot be obtained. Therefore, the average spherical equivalent radius of the alloy carbides in the ferrite is set to be greater than 0.5 nm. The average spherical equivalent radius of the alloy carbides in the ferrite is preferably greater than 1.0 nm.
[0147] On the other hand, when the average spherical equivalent radius of the alloy carbide in the ferrite is more than 10.0nm, the strength of the ferrite cannot be fully improved, and the hardness difference between the grains causes cracks to form at the tip of the shearing tool in the very early stage of the shearing process, forming a fracture surface, and then forming a shear surface again. As a result, it becomes easy to form a secondary shear surface, so the desired shear workability cannot be obtained in the hot-rolled steel sheet. Therefore, the average spherical equivalent radius of the alloy carbide in the ferrite is set to less than 10.0nm. The average spherical equivalent radius of the alloy carbide in the ferrite is preferably less than 8.0nm, less than 6.0nm, less than 4.0nm, and more preferably less than 2.0nm.
[0148] Average number density of alloy carbides in ferrite: 0.10×10 16 Pieces / cm 3 Above and less than 1.45×10 16 Pieces / cm 3
[0149] The average number density of alloy carbides in ferrite is less than 0.10×10 16 Pieces / cm 3 or 1.45×10 16 Pieces / cm 3 If the value is above 0.10×10, the strength of ferrite against repeated deformation cannot be sufficiently improved, and the desired fatigue strength cannot be obtained. Therefore, the average number density of alloy carbides in ferrite is set to 0.10×10 16 Pieces / cm 3 Above and less than 1.45×10 16 Pieces / cm 3 The average number density of alloy carbides in ferrite is preferably 0.50×10 16 Pieces / cm 3 More preferably, 1.00×10 16 Pieces / cm 3 In addition, the average number density of alloy carbides in ferrite is preferably 1.40×10 16 Pieces / cm 3 Below, more preferably 1.20×10 16 Pieces / cm 3 Below, more preferably 1.10×10 16 Pieces / cm 3 the following.
[0150] In addition, in this embodiment, alloy carbide refers to carbide containing one or two or more of Ti, Nb, Mo and V.
[0151] The sphere equivalent radius and number density of alloy carbides in ferrite are measured using a three-dimensional atom probe. The three-dimensional atom probe measurement sets the laser wavelength (λ) to 355 nm, the laser power to 30 pJ, and the temperature of the needle-shaped test piece to 50 K. The device used for the three-dimensional atom probe measurement is not particularly limited. An example of a three-dimensional atom probe measurement device is the trade name LEAP4000XHR manufactured by AMETEK, Inc.
[0152] For the ferrite grains in the above-mentioned EBSD-based observation field where the area ratio of each structure is measured, a sample is obtained using a FIB (focused ion beam) device. By processing the sample into a needle shape using a well-known method, the spherical equivalent radius and number density of fine precipitates with a spherical equivalent radius ranging from less than 1 nm to several 10 nm can be accurately measured using a three-dimensional atom probe. The number density of the precipitates can be obtained by dividing the number of precipitates contained in the area measured by the three-dimensional atom probe by the volume of the measurement area for the precipitates identified as alloy carbides using the method described later.
[0153] The total volume of the precipitates in the measurement region is obtained by dividing the total number of atoms of the alloying elements (Ti, Nb, Mo, V, C) contained in all precipitates in the measurement region by the atomic density of the alloy carbides. The volume of the precipitates is obtained by dividing the total volume of the precipitates by the number of precipitates. Based on the volume of the obtained precipitates, the spherical equivalent radius is calculated assuming that the precipitates are spherical.
[0154] By using a 30000nm 3 The above method is implemented for more than 5 measurement data of the above measurement area volume to obtain the average number density and the average sphere equivalent radius. It should be noted that the area where Ga introduced during FIB processing is less than 0.025at% is used as the observation area, and the area where Ga is mixed with more than 0.025at% is excluded from the measurement area. Regarding the confirmation of the Ga amount, the 1D Concentration Profile (one-dimensional concentration distribution) function of the data analysis software IVAS 3.6.14 (manufactured by CAMECA Instruments Inc.) can be used to confirm the Ga amount in the longitudinal direction of the needle sample.
[0155] It should be noted that whether the observed precipitates are alloy carbides was determined by using the Cluster Analysis function of the analysis software IVAS 3.6.14 on the data acquired by the three-dimensional atom probe. max =1.2nm、Order(times)=10、N min =10, L=0.5 nm, d erosion=0.5 nm were used as analysis parameters, and the precipitates identified as Cluster were identified as alloy carbides.
[0156] E value: 10.7 or above
[0157] I value: 1.020 or above
[0158] In order to suppress the generation of secondary shear planes, it is important to form a fracture surface after the shear plane is fully formed, and it is necessary to suppress the generation of cracks from the tip of the tool at an early stage during shearing. For this purpose, it is important that the periodicity of the metal structure is low and the uniformity of the metal structure is high. In this embodiment, the generation of secondary shear planes is suppressed by controlling the E (Entropy) value representing the periodicity of the metal structure and the I (Inverse difference normalized) value representing the uniformity of the metal structure.
[0159] The E value represents the periodicity of the metal structure. When the brightness is arranged periodically due to the influence of banded structure formation, that is, when the periodicity of the metal structure is high, the E value decreases. The present embodiment needs to form a metal structure with low periodicity, so it is necessary to increase the E value. When the E value is less than 10.7, it becomes easy to generate a secondary shear surface. Taking the periodically arranged structure as the starting point, cracks are generated from the tip of the shearing tool in the very early stage of the shearing process, forming a fracture surface, and then a shear surface is formed again. It is estimated that this makes it easy to generate a secondary shear surface. Therefore, the E value is set to 10.7 or more. Preferably, it is 10.8 or more, and more preferably, it is 11.0 or more. The higher the E value, the more preferred it is. There is no special upper limit, and it can be set to less than 13.0, less than 12.5 or less than 12.0.
[0160] The I value represents the uniformity of the metal structure, and the larger the area of the region with a certain brightness, the higher the value. A high I value indicates that the uniformity of the metal structure is high. The present embodiment needs to form a metal structure with high uniformity, so it is necessary to increase the I value. When the I value is less than 1.020, due to the influence of the precipitates in the grains and the hardness distribution caused by the difference in element concentration, cracks are generated from the tip of the shearing tool in the very early stage of the shearing process, a fracture surface is formed, and then a shear surface is formed again. It is estimated that this makes it easy to generate a secondary shear surface. Therefore, the I value is set to be greater than 1.020. Preferably, it is greater than 1.025, and more preferably, it is greater than 1.030. The higher the I value, the more preferred it is. There is no special upper limit, and it can be set to less than 1.200, less than 1.150, or less than 1.100.
[0161] The E value and I value can be obtained by the following method.
[0162] In this embodiment, the imaging area of the SEM image taken to calculate the E value and the I value is 200 μm × 200 μm at the position 1 / 4 of the end face in the plate width direction, on the cross section parallel to the rolling direction, and centered at the position 1 / 4 of the surface in the plate thickness direction, and the number of observation fields is 5. The SEM image is taken using a SU-6600 Schottky electron gun manufactured by Hitachi High-Technologies Corporation, the emitter is tungsten, and the acceleration voltage is set to 1.5 kV. Under the above settings, the SEM image is output at a magnification of 1000 times and a grayscale of 256 levels.
[0163] Next, for the image obtained by cutting out an area of 880×880 pixels from the obtained SEM image, a smoothing process was performed with the contrast enhancement limit ratio set to 2.0 and the tile grid size set to 8×8 as described in non-patent document 3. The SEM image after smoothing was rotated counterclockwise every 1 degree from 0 to 179 degrees, excluding 90 degrees, and one image was produced every 1 degree, thereby obtaining a total of 179 images. Next, the gray level co-occurrence matrix method (GLCM method) described in non-patent document 1 was used for each of these 179 images to obtain the frequency value of the brightness between adjacent pixels in the form of a matrix.
[0164] The matrix of 179 frequency values obtained by the above method is expressed as p, with k as the rotation angle from the original image. k (k = 0...89, 91, ...179). For each image, the generated p k After summing up all k (k = 0 ... 89, 91 ... 179), a 256 × 256 matrix P is calculated and normalized so that the sum of each component is 1. Furthermore, the E value and the I value are calculated respectively using the following formula (1) and formula (2) described in non-patent document 2. It should be noted that the average value is calculated by measuring the entire field of view.
[0165] In the following equations (1) and (2), P(i, j) is the gray level co-occurrence matrix, and the value of the i-th row and j-th column of the matrix P is recorded as P(i, j). It should be noted that, as mentioned above, the 256×256 matrix P is used for calculation, so if you want to emphasize this point, the following equation (1) can be corrected to the following equation (1'), and the following equation (2) can be corrected to the following equation (2'). In the following equations (1') and (2'), the value of the i-th row and j-th column of the matrix P is recorded as P ij .
[0166] [Mathematical formula 1]
[0167] E=-∑ i ∑ i p(i,j).log(p(i,j)) (1)
[0168] [Mathematical formula 2]
[0169]
[0170] [Mathematical formula 3]
[0171]
[0172] [Formula 4]
[0173]
[0174] Standard deviation of Mn concentration: 0.60 mass % or less
[0175] The standard deviation of the Mn concentration of the hot-rolled steel sheet of the present embodiment is 0.60 mass % or less. Thus, the hard phase can be evenly dispersed, and cracks can be prevented from being generated from the tip of the shearing tool in the very early stage of the shearing process. As a result, the generation of secondary shear surfaces can be suppressed. The standard deviation of the Mn concentration is preferably 0.50 mass % or less, and more preferably 0.47 mass % or less. From the perspective of suppressing excessive burrs, the lower limit of the standard deviation of the Mn concentration is the smaller the value, the more ideal it is. Due to the limitations of the manufacturing process, the actual lower limit is 0.10 mass %.
[0176] The standard deviation of the Mn concentration can be obtained by the following method.
[0177] First, at a position 1 / 4 away from the end face in the width direction of the plate, on a cross section parallel to the rolling direction, a sample is obtained in such a way that an area 1 / 4 away from the surface in the thickness direction of the plate can be observed. Although it also depends on the measuring device, the sample is of a size that can be observed in the rolling direction of about 10 mm. Next, after the above-mentioned sample is mirror-polished, the standard deviation of the Mn concentration is measured using an electron probe microanalyzer (EPMA). Regarding the measurement conditions, the acceleration voltage is set to 15 kV, the magnification is set to 5000 times, and the distribution images of more than 40,000 areas of 20 μm in the rolling direction and 20 μm in the plate thickness direction are measured at a measurement interval of 0.1 μm. Next, the standard deviation is calculated based on the Mn concentration obtained from all the measurement points, thereby obtaining the standard deviation of the Mn concentration.
[0178] Tensile properties
[0179] The tensile strength characteristics (tensile strength, total elongation) of the mechanical properties of the hot-rolled steel sheet were evaluated in accordance with JIS Z2241: 2011. The test piece used was the No. 5 test piece of JIS Z2241: 2011. The test piece was obtained at a position 1 / 4 of the distance from the end face in the plate width direction of the hot-rolled steel sheet, and the plate width direction was taken as the longitudinal direction of the test piece.
[0180] The hot-rolled steel sheet of this embodiment preferably has a tensile (maximum) strength of 980 MPa or more. The tensile strength is more preferably 1000 MPa or more. By setting the tensile strength to 980 MPa or more, the application parts are not limited, which can greatly contribute to the lightweighting of the vehicle body. The upper limit does not need to be particularly limited, and from the perspective of suppressing mold wear, it can be set to 1780 MPa.
[0181] The total elongation is preferably set to 10.0% or more, and the product of the tensile strength and the total elongation (TS×El) is preferably set to 13000 MPa·% or more. The total elongation is more preferably set to 11.0% or more, and further preferably set to 13.0% or more. In addition, the product of the tensile strength and the total elongation is more preferably set to 14000 MPa·% or more, and further preferably set to 15000 MPa·% or more.
[0182] By setting the total elongation to 10.0% or more and the product of the tensile strength and the total elongation to 13000 MPa·% or more, the application parts are not limited and it is possible to greatly contribute to the weight reduction of the vehicle body.
[0183] Fatigue properties
[0184] If the material solidifies during repeated deformation, the amount of plastic deformation during repeated deformation will decrease, so there is a tendency for fatigue life to be extended. Therefore, it is preferred that the material solidifies during repeated deformation. Whether solidification occurs during repeated deformation can be judged by the following method.
[0185] At a position 1 / 4 of the distance from the end face in the width direction of the hot-rolled steel plate, a test piece marked "1-15" is obtained in accordance with JIS Z2275-1978 in such a way that the width direction of the plate becomes the longitudinal direction of the test piece. Using this test piece, a plane bending fatigue test is carried out in accordance with JIS Z2275-1978 with a repetitive stress of more than 3 million times and less than 10 million times of fracture repetition. The torque in the fatigue test or the value of the strain gauge attached to the test piece is measured to evaluate the change in repetitive stress. The repetitive stress at 100 repetitions is used as the reference stress. In the range of 100,000 to 1,000,000 repetitions, when the repetitive stress is more than 5% higher than the above-mentioned reference stress, it can be judged that repeated solidification has occurred and it is a hot-rolled steel plate with excellent fatigue properties.
[0186] Plate thickness
[0187] The plate thickness of the hot-rolled steel plate of the present embodiment is not particularly limited, and can be set to 0.5 to 8.0 mm. When the plate thickness of the hot-rolled steel plate is less than 0.5 mm, it becomes difficult to ensure the rolling end temperature, and the rolling load becomes too large, which sometimes makes it difficult to perform hot rolling. Therefore, the plate thickness of the hot-rolled steel plate of the present embodiment can be set to 0.5 mm or more. Preferably, it is 1.2 mm or more or 1.4 mm or more.
[0188] On the other hand, when the plate thickness is greater than 8.0 mm, it may be difficult to refine the metal structure and obtain the above metal structure. Therefore, the plate thickness may be set to 8.0 mm or less, preferably 6.0 mm or less.
[0189] Plating
[0190] The hot rolled steel sheet of the present embodiment with the above-mentioned chemical composition and metal structure can be provided with a coating on the surface for the purpose of improving corrosion resistance, etc., to make a surface treated steel sheet. The coating can be an electroplated layer or a hot dip coating. As the electroplated layer, examples include electrogalvanizing, electroplating Zn-Ni alloy, etc. As the hot dip coating, examples include hot dip galvanizing, alloyed hot dip galvanizing, hot dip aluminum plating, hot dip Zn-Al alloy plating, hot dip Zn-Al-Mg alloy plating, hot dip Zn-Al-Mg-Si alloy plating, etc. The coating adhesion amount is not particularly limited, and the same as in the past can be adopted. In addition, suitable chemical conversion treatment (such as coating and drying of a chromium-free chemical conversion treatment solution of a silicate system) can also be implemented after plating to further improve corrosion resistance.
[0191] Manufacturing conditions
[0192] A suitable method for producing the hot-rolled steel sheet of the present embodiment having the above-mentioned chemical composition and metal structure is as follows.
[0193] To obtain the hot-rolled steel sheet of the present embodiment, it is effective to heat the slab under predetermined conditions, perform hot rolling, perform accelerated cooling to a predetermined temperature range, and then perform slow cooling to control the cooling history until coiling.
[0194] The preferred method for manufacturing the hot-rolled steel sheet of the present embodiment sequentially performs the following steps (1) to (10). It should be noted that the temperature of the slab and the temperature of the steel sheet in the present embodiment refer to the surface temperature of the slab and the surface temperature of the steel sheet. In addition, stress refers to the tension applied to the steel sheet in the rolling direction. The stress can be controlled by adjusting the rotation speed of the rolling stand and the coiling device, and can be obtained by dividing the measured load in the rolling direction by the cross-sectional area of the plate through which the plate is passed.
[0195] (1) After the slab is held in a temperature range of 700° C. to 850° C. for 900 seconds or more, it is further heated and held in a temperature range of 1100° C. or more for 6000 seconds or more.
[0196] (2) Hot rolling is performed in a temperature range of 850° C. to 1100° C. to reduce the plate thickness by 90% or more in total.
[0197] (3) The steel sheet is rolled one stage before the final stage at a temperature of 900° C. or higher and less than 1010° C., and a stress of 170 kPa or higher is applied to the steel sheet after the hot rolling one stage before the final stage and before the final stage.
[0198] (4) The rolling reduction rate in the final stage of hot rolling is set to 8% or more, and the hot rolling is completed so that the rolling end temperature Tf is 900°C or more and less than 1010°C.
[0199] (5) Soft reduction is performed in a temperature range of 840°C or higher and lower than 900°C to reduce the plate thickness by a total of 5% or higher and lower than 8%.
[0200] (6) The stress applied to the steel sheet after the final rolling of hot rolling and before the initial rolling of light reduction and the stress applied to the steel sheet after the final rolling of light reduction and until the steel sheet is cooled to 800° C. are set to less than 200 kPa.
[0201] (7) After the soft reduction is completed, accelerated cooling is performed at an average cooling rate of 50°C / sec or more to a temperature range of 600°C or more and less than 680°C.
[0202] (8) Slow cooling is performed in a temperature range of 600°C to less than 680°C at an average cooling rate of less than 5°C / s for 2.0 seconds or more.
[0203] (9) Cooling is performed at an average cooling rate of 50°C / s or more to a temperature range of 350°C or less.
[0204] (10) Coil in a temperature range below 350°C.
[0205] By adopting the above-mentioned manufacturing method, a hot-rolled steel sheet having high strength and excellent ductility, fatigue properties and shear workability can be stably manufactured. That is, by appropriately controlling the slab heating conditions and hot rolling conditions, it is possible to reduce the Mn segregation and equiaxed austenite before the transformation, and in combination with the cooling conditions after hot rolling described later, a hot-rolled steel sheet having a desired metal structure can be stably manufactured.
[0206] (1) Slab, slab temperature during hot rolling, and holding time
[0207] The slabs for hot rolling can be slabs obtained by continuous casting, slabs obtained by casting-blowing, etc., which are subjected to hot working or cold working as needed. The slabs for hot rolling are preferably kept in a temperature range of 700°C to 850°C for more than 900 seconds when the slabs are heated, and then further heated and kept in a temperature range of 1100°C or more for more than 6000 seconds.
[0208] It should be noted that when the temperature is maintained in the range of 700°C to 850°C, the temperature of the steel plate may be varied in the temperature range or kept constant. Furthermore, when the temperature is maintained at 1100°C or higher, the temperature of the steel plate may be varied in the temperature range of 1100°C or higher or kept constant.
[0209] In the austenite transformation in the temperature range of 700°C to 850°C, Mn is distributed between ferrite and austenite, and by extending the transformation time, Mn can be diffused in the ferrite region. As a result, the Mn microsegregation concentrated in the slab can be eliminated, and the standard deviation of the Mn concentration can be significantly reduced. Therefore, it is preferred to maintain the temperature range of 700°C to 850°C for more than 900 seconds. In addition, by maintaining the temperature range of 1100°C or more for more than 6000 seconds, the standard deviation of the Mn concentration can be significantly reduced.
[0210] Hot rolling is preferably performed using a reversing mill or a tandem mill as a multi-pass rolling. In particular, from the perspective of industrial productivity and the stress load on the steel plate during rolling, at least the last two stages are preferably hot rolled using a tandem mill.
[0211] (2) Hot rolling reduction rate: The plate thickness is reduced by 90% or more in the temperature range of 850°C to 1100°C.
[0212] By performing hot rolling with a total plate thickness reduction of 90% or more in a temperature range of 850°C to 1100°C, the recrystallized austenite grains can be mainly refined, and the accumulation of strain energy in the non-recrystallized austenite grains can be promoted. In addition, the recrystallization of austenite and the atomic diffusion of Mn can be promoted, and the standard deviation of the Mn concentration can be reduced. Therefore, it is preferred to perform hot rolling with a total plate thickness reduction of 90% or more in a temperature range of 850°C to 1100°C.
[0213] It should be noted that the total plate thickness reduction in the temperature range of 850°C or higher and 1100°C or lower is calculated by assuming that the plate thickness before the initial rolling in the rolling in this temperature range is t 0 , let the exit plate thickness after rolling in the final stage of rolling in this temperature range be t 1 When , it can be expressed as {(t 0 -t 1 ) / t 0}×100(%).
[0214] (3) Rolling temperature from the final stage to the previous stage: 900°C or higher and less than 1010°C; stress after hot rolling from the final stage to the previous stage and before hot rolling: 170 kPa or higher
[0215] It is preferred that the rolling be performed at 900°C or higher and lower than 1010°C, and the stress applied to the steel sheet after the hot rolling and before the final rolling is set to 170 kPa or higher. This can reduce the {110} <001> The number of grains with the same crystal orientation. <001> It is a crystal orientation that is difficult to recrystallize, so by suppressing the formation of this crystal orientation, the recrystallization caused by the final stage of pressing can be effectively promoted. As a result, the banded structure of the hot-rolled steel plate can be improved, the periodicity of the metal structure can be reduced, and the E value can be increased. When the stress on the steel plate is less than 170kPa, the desired E value may not be obtained. The stress on the steel plate is more preferably above 190kPa. It should be noted that the stress on the steel plate refers to the tension of the longitudinal load on the steel plate, which can be controlled by adjusting the roller rotation speed during continuous rolling.
[0216] The upper limit of the stress applied to the steel sheet is not particularly limited, but can be set to 350 kPa or less.
[0217] (4) Reduction ratio of the final stage of hot rolling: 8% or more, hot rolling end temperature Tf: 900°C or more and less than 1010°C
[0218] It is preferred that the reduction rate of the final stage of hot rolling is set to 8% or more, and the hot rolling end temperature Tf is set to 900°C or more. By setting the reduction rate of the final stage of hot rolling to 8% or more, the recrystallization caused by the reduction of the final stage can be promoted. As a result, the banded structure of the hot-rolled steel sheet can be improved, the periodicity of the metal structure can be reduced, and the E value can be increased. By setting the hot rolling end temperature Tf to 900°C or more, the excessive increase in the number of ferrite nucleation sites in austenite can be suppressed. As a result, the formation of ferrite in the final structure (the metal structure of the hot-rolled steel sheet after manufacture) can be suppressed, and the desired strength can be obtained. In addition, by setting Tf to less than 1010°C, the coarsening of the austenite grain size can be suppressed, the periodicity of the metal structure can be reduced, and the desired E value can be obtained. It should be noted that the upper limit of the reduction rate of the final stage of hot rolling is not particularly limited, and can be set to 30% or less, preferably set to 20% or less, and further to 15% or less.
[0219] (5) Soft reduction is performed in a temperature range of 840°C or higher and lower than 900°C to reduce the plate thickness by a total of 5% or higher and lower than 8%.
[0220] After the final stage of hot rolling, soft reduction is preferably performed in a temperature range of 840° C. to less than 900° C. to reduce the plate thickness by 5% to less than 8%. This allows the average spherical equivalent radius and average number density of alloy carbides in ferrite to be controlled to desired values.
[0221] The soft reduction can be carried out, for example, in the final section of the finishing mill, or by introducing a new reduction device between the finishing mill and the cooling bed.
[0222] It should be noted that, regarding the total plate thickness reduction by soft rolling, the plate thickness before the initial rolling by soft rolling is assumed to be t 0 , Assume that the final thickness of the plate after rolling under light pressure is t 1 When , it can be expressed as {(t 0 -t 1 ) / t 0}×100(%).
[0223] (6) Stress applied to the steel sheet after the final rolling of hot rolling and before the initial rolling of light pressing, and stress applied to the steel sheet after the final rolling of light pressing and before the steel sheet is cooled to 800°C: less than 200 kPa
[0224] The stress applied to the steel plate after the final section of hot rolling and before the initial rolling of light pressing, and the stress applied to the steel plate after the final section of light pressing and until the steel plate is cooled to 800°C are preferably set to less than 200 kPa, respectively. By setting the stress applied to the steel plate to less than 200 kPa at the above-mentioned locations, the recrystallization of austenite is preferentially advanced along the rolling direction, and the periodic increase of the metal structure can be suppressed. As a result, the desired E value can be obtained. The stress applied to the steel plate at the above-mentioned locations is more preferably less than 180 kPa, respectively.
[0225] (7) After the soft pressing is completed, accelerated cooling is performed at an average cooling rate of 50°C / s or more to a temperature range of 600°C or more and less than 680°C.
[0226] In order to suppress the growth of austenite grains refined by hot rolling, it is preferred that after the soft reduction, accelerated cooling is performed at an average cooling rate of 50°C / s or more to a temperature range below 680°C. By performing accelerated cooling to a temperature range below 680°C, the average number density of alloy carbides in ferrite can be reduced to less than 1.45×10 16 Pieces / cm 3 Furthermore, by setting the average cooling rate of accelerated cooling to a temperature range of 600° C. or higher and lower than 680° C. to 50° C. / sec or higher, it is possible to suppress excessive formation of pearlite.
[0227] It should be noted that the average cooling rate mentioned here refers to the value obtained by dividing the temperature drop of the steel plate from the start of accelerated cooling (when the steel plate is introduced from the cooling equipment) to the end of accelerated cooling (when the steel plate is unloaded from the cooling equipment) by the time required from the start of accelerated cooling to the end of accelerated cooling.
[0228] There is no particular upper limit on the cooling rate. When the cooling rate is increased, the cooling equipment scale increases and the equipment cost increases. Therefore, considering the equipment cost, the average cooling rate is preferably 300°C / sec or less. In addition, in order to make the area ratio of ferrite 15.0% or more and the average number density of alloy carbides in ferrite 0.10×10 16 Pieces / cm 3 In the above, the average spherical equivalent radius of the alloy carbides in the ferrite is set to 0.5 nm or more, and the cooling stop temperature of the accelerated cooling is preferably set to 600° C. or more.
[0229] In order to realize the above-mentioned average cooling rate, cooling at a high average cooling rate may be performed after the soft reduction is completed, for example, by spraying cooling water onto the surface of the steel sheet.
[0230] (8) Slow cooling at an average cooling rate of less than 5°C / s for 2.0 seconds or more in a temperature range of 600°C to less than 680°C
[0231] By performing slow cooling at an average cooling rate of less than 5°C / s for 2.0 seconds or more in a temperature range of 600°C to less than 680°C, a desired amount of ferrite can be obtained. In addition, the number density of alloy carbides in ferrite can be controlled to a desired amount.
[0232] The average cooling rate referred to here is a value obtained by dividing the temperature drop of the steel plate from the cooling stop temperature of the accelerated cooling to the slow cooling stop temperature by the time required from the stop of the accelerated cooling to the stop of the slow cooling.
[0233] The time for slow cooling is preferably 3.0 seconds or more. The upper limit of the time for slow cooling is determined by the equipment layout and can be set to be approximately less than 10.0 seconds. In addition, the lower limit of the average cooling rate of slow cooling is not particularly set, but since heating without cooling will be accompanied by a large investment in equipment, it can be set to 0°C / s or more.
[0234] (9) Average cooling rate to coiling temperature: 50°C / sec or more
[0235] In order to suppress the area ratio of pearlite and obtain the desired strength, it is preferred to set the average cooling rate from the cooling stop temperature of slow cooling to the coiling temperature to 50°C / sec or more. This allows the parent phase structure to be hard, and further allows the average spherical equivalent radius and average number density of alloy carbides in the desired ferrite to be controlled to desired values.
[0236] It should be noted that the average cooling rate referred to here is a value obtained by dividing the temperature drop of the steel plate from the cooling stop temperature of slow cooling at an average cooling rate of less than 5°C / s to the coiling temperature by the time required from the stop of slow cooling at an average cooling rate of less than 5°C / s to coiling.
[0237] (10) Coiling temperature: below 350°C
[0238] The coiling temperature is preferably set to 350° C. or lower. By setting the coiling temperature to 350° C. or lower, the precipitation amount of iron carbides can be reduced and the hardness distribution unevenness in the hard phase can be reduced. As a result, a desired I value can be obtained.
[0239] Example
[0240] Next, the effect of one solution of the present invention is described in more detail through an embodiment, and the conditions in the embodiment are a conditional example adopted to confirm the feasibility and effect of the present invention, and the present invention is not limited to this conditional example. The present invention can adopt various conditions without departing from the gist of the present invention and achieving the purpose of the present invention.
[0241] Steels having the chemical compositions shown in Tables 1 and 2 were melted and continuously cast to produce slabs having a thickness of 240 to 300 mm. The obtained slabs were used to produce hot-rolled steel sheets shown in Tables 5A and 6B under the production conditions shown in Tables 3A to 4B.
[0242] It should be noted that the average cooling rate of slow cooling is set to less than 5°C / s. In addition, since the coiling temperature of 50°C described in Table 4A and Table 4B is the lower limit of measurement, the actual coiling temperature of the example described as 50°C is 50°C or less. In addition, the hot rolling is performed at 900°C or more and less than 1010°C from the final stage to the previous stage.
[0243] For the obtained hot-rolled steel sheet, the area ratio of the metal structure, E value, I value, standard deviation of Mn concentration, average spherical equivalent radius and average number density of alloy carbides in ferrite, tensile strength TS, and total elongation El were obtained by the above method. In addition, fatigue properties were evaluated by performing plane bending fatigue properties using the above method. The obtained measurement results are shown in Tables 5A to 6B.
[0244] Evaluation method of characteristics of hot-rolled steel sheets
[0245] Tensile properties
[0246] When the tensile strength TS is 980 MPa or more, the total elongation EI is 10.0% or more, and the tensile strength T×total elongation EI is 13000 MPa·% or more, it is considered to be a hot-rolled steel sheet with high strength and excellent ductility and is judged to be qualified. If any one of the above is not satisfied, it is considered not to be a hot-rolled steel sheet with high strength and is judged to be unqualified.
[0247] Fatigue properties
[0248] When a plane bending fatigue test is conducted using the above method and the repetitive stress is 5% or more higher than the reference stress within the range of 100,000 to 1,000,000 repetitions, it is considered that repeated solidification has occurred and the hot-rolled steel has excellent fatigue properties and is judged to be qualified.
[0249] On the other hand, when the repetitive stress is not 5% or more higher than the reference stress within the range of 100,000 to 1,000,000 repetitions, it is considered that repetitive hardening has not occurred and the hot-rolled steel sheet does not have excellent fatigue properties and is judged as unacceptable.
[0250] The examples judged as acceptable are described as “Good” in the fatigue property column of the table, and the examples judged as unacceptable are described as “NG” in the table.
[0251] Shear processability (secondary shear surface evaluation)
[0252] The shear workability of the hot-rolled steel sheet was evaluated by a punching test.
[0253] Three punching holes were made for each example with a hole diameter of 10 mm, a gap of 10%, and a punching speed of 3 m / s. Next, the plate thickness section at right angles to the rolling direction and the plate thickness section parallel to the rolling direction of the punching hole were respectively embedded with resin, and the cross-sectional shape was photographed using a scanning electron microscope. The obtained observation photographs can be observed as follows: Figure 1 or Figure 2 The shear end face shown. It should be noted that Figure 1 This is an example of a sheared end surface of a hot-rolled steel sheet according to an example of the present invention. Figure 2 This is an example of a sheared end surface of a hot-rolled steel sheet of a comparative example. Figure 1 It is the shear end surface of collapsed edge-shear surface-fracture surface-burr. On the other hand, Figure 2 The shear end surface is a collapsed edge-shear surface-fracture surface-shear surface-fracture surface-burr. Here, the collapsed edge refers to the area of the R-shaped smooth surface, the shear surface refers to the area of the punched end surface separated by shear deformation, the fracture surface refers to the area of the punched end surface separated by cracks generated near the blade tip, and the burr refers to the surface with protrusions protruding from the lower surface of the hot-rolled steel plate.
[0254] In the obtained shear end faces, two faces perpendicular to the rolling direction and two faces parallel to the rolling direction, for example, when the following Figure 2 In the case of the shear surface-fracture surface-shear surface shown in the table, it is judged that a secondary shear surface is formed. For each punched hole, 4 surfaces, a total of 12 surfaces, are observed. If there is no secondary shear surface on any surface, it is considered to be a hot-rolled steel sheet with excellent shear workability and is judged to be qualified. On the other hand, if only one secondary shear surface is formed, it is considered not to be a hot-rolled steel sheet with excellent shear workability and is judged to be unqualified. For the examples judged to be qualified, the shear workability column in the table is recorded as "Good", and for the examples judged to be unqualified, they are recorded as "NG" in the table.
[0255] surface
[0256]
[0257] The underline indicates outside the scope of the present invention.
[0258]
[0259] [Table 3A]
[0260]
[0261] The underlined elements are outside the scope of the present invention or the production conditions are not preferred.
[0262] [Table 3B]
[0263]
[0264] The underlined elements are outside the scope of the present invention or the production conditions are not preferred.
[0265]
[0266]
[0267]
[0268]
[0269] [Table 6A]
[0270]
[0271] The underlined elements are outside the scope of the present invention or the production conditions are not preferred.
[0272] [Table 6B]
[0273]
[0274] The underlined elements are outside the range at the time of the present invention or the production conditions are not preferred.
[0275] As can be seen from Tables 5A to 6B, the hot-rolled steel sheets of the examples of the present invention have high strength and excellent ductility, fatigue properties, and shear workability.
[0276] On the other hand, it is understood that the hot-rolled steel sheets of the comparative examples do not have any one or more of the above-mentioned characteristics.
Claims
1. A hot rolled steel plate, characterized in that: The chemical composition by mass% contains: C:0.050~0.250%、 Si: 0.05-3.00%, Mn: 1.00~4.00%, One or more of Ti, Nb and V: 0.060 to 0.500% in total, Sol.Al: 0.001~2.000%, P: 0.100% or less, S: 0.0300% or less, N: 0.1000% or less, O: 0.0100% or less, Cu: 0-2.00%, Cr:0~2.00%、 Mo: 0-1.00%, Ni: 0-2.00%, B:0~0.0100%、 Ca: 0~0.0200%, Mg: 0~0.0200%, REM: 0~0.1000%、 Bi: 0~0.0200%, As: 0~0.100%, One or more of Zr, Co, Zn and W: 0 to 1.00% in total, and Sn: 0 to 0.05%, The remainder contains Fe and impurities, Metallic structure is calculated by area %, Retained austenite is less than 3.0%, Ferrite is 15.0% or more and less than 60.0%, Pearlite is less than 5.0%, The average spherical equivalent radius of the alloy carbides in the ferrite is greater than 0.5 nm and less than 10.0 nm, and the average number density is 0.10×10 16 Pieces / cm 3 Above and less than 1.45×10 16 Pieces / cm 3 , The E value indicating the periodicity of the metal structure is 10.7 or more, The I value indicating the homogeneity of the metal structure is 1.020 or more, The standard deviation of the Mn concentration was 0.60 mass % or less.
2. The hot rolled steel sheet according to claim 1, characterized in that: The chemical composition contains, by mass%, one or more selected from the group consisting of the following elements: Cu: 0.01-2.00%, Cr:0.01~2.00%、 Mo: 0.01~1.00%, Ni: 0.02-2.00%, B:0.0001~0.0100%、 Ca: 0.0005~0.0200%, Mg: 0.0005~0.0200%, REM: 0.0005~0.1000%、 Bi: 0.0005 to 0.0200%, and As: 0.001~0.100%.
Citation Information
Patent Citations
Cold rolled steel sheet excellent in blanking property and its production
JP1998168544A
High strength steel sheet having excellent elongation and stretch-flange formability
JP2005179703A
Composition
JP2022135960A